Convective Aggregation and the Amplification of Tropical Precipitation Extremes - Ni Dai; Brian J. Soden (AGU Advances, 2020)
Abstract It is widely believed that precipitation extremes will increase in response to a warming climate, as inferred from both observations and numerical simulations. In the absence of changes in atmospheric circulations, extreme precipitation is expected to increase in already‐moist regions along a thermodynamical Clausius‐Clapeyron scaling. However, within the tropics, the sensitivities inferred from observations of interannual variability are roughly twice as large, implying an unknown contribution from atmospheric dynamics. In this paper, we use satellite observations and climate model simulations to investigate the relationship between convective aggregation and precipitation and the role that convective aggregation plays in amplifying the response of tropical precipitation extremes to interannual surface warming. We find that the occurrence of heavier precipitation coincides with a higher degree of convective aggregation. Extreme precipitation events and convective aggregation tend to increase during warm, El Niño events compared to colder, La Niña events. Although both the frequency and intensity of heavy to extreme precipitation can increase with increased aggregation during El Niño, the changes in frequency are more consistent among the observations and models than changes in intensity. In both the observations and models, increases in large‐scale convective aggregation contribute to roughly one third of the increase in extreme precipitation frequency due to interannual warming by shifting moderate‐to‐heavy precipitation events to more extreme precipitation intensities. The linkages between convective aggregation and precipitation extremes considered here offer insights into their potential response to anthropogenic warming.